Electrolyte profiles with induced hypothermia: A sub study of a clinical trial evaluating the duration of hypothermia after cardiac arrest. Issue 5 (28th March 2022) - Kirkegaard, Hans; Grejs, Anders M.; Gudbjerg, Simon; Duez, Christophe; Jeppesen, Anni; Hassager, Christian; Laitio, Timo; Storm, Christian; Taccone, Fabio Silvio; Skrifvars, Markus B.; Søreide, Eldar
Abstract: Background: Electrolyte disturbances can result from targeted temperature treatment (TTM) in out‐of‐hospital cardiac arrest (OHCA) patients. This study explores electrolyte changes in blood and urine in OHCA patients treated with TTM. Methods: This is a sub‐study of the TTH48 trial, with the inclusion of 310 unconscious OHCA patients treated with TTM at 33°C for 24 or 48 h. Over a three‐day period, serum concentrations were obtained on sodium potassium, chloride, ionized calcium, magnesium and phosphate, as were results from a 24‐h diuresis and urine electrolyte concentration and excretion. Changes over time were analysed with a mixed‐model multivariate analysis of variance with repeated measurements. Results: On admission, mean ± SD sodium concentration was 138 ± 3.5 mmol/l, which increased slightly but significantly ( p  < .05) during the first 24 h. Magnesium concentration stayed within the reference interval. Median ionized calcium concentration increased from 1.11 (IQR 1.1–1.2) mmol/l during the first 24 h ( p  < .05), whereas median phosphate concentration dropped to 1.02 (IQR 0.8–1.2) mmol/l ( p  < .05) and stayed low. During rewarming, potassium concentrations increased, and magnesium and ionizes calcium concentration decreased ( p  < .05). Median 24‐h diuresis results on days one and two were 2198 and 2048 ml respectively, and the electrolyte excretion mostly stayed low in the reference interval. Conclusions: Electrolytes mostly remained within the reference interval. A temporal change occurred in potassium, magnesium and calcium concentrations with TTM's different phases. No hypothermia effect on diuresis was detected, and urine excretion of electrolytes mostly stayed low.